The Brussels-Capital Region. Increasing the Density of Urban Spaces and Preserving the Quality of Life - Pankratieva, Ioulia (project baikal, 2013)
Since its foundation in 1989, Region of Brussels Capital has its own government and conducts an independent urban policy. With the constant increase in population the main objectives for the Region are concentrated on development of housing and infrastructure objects, transport security, and improvement of functioning of urban structures.Urban policy is based on the Regional Plan for Sustainable Development (Plan Régional de Développement Durable - PRDD), which is a strategic tool for urban planning and deals with a wide range of issues related to the economy, demographics, construction, transport.A new Regional Plan for Sustainable Development was adopted in December 2012. It will direct the development of the Region for the next 25 years. Densification of urban environment was highlighted in a separate section. Development of this section was entrusted to the Bureau COOPARCH.ru.